Analyzing bank "black boxes": A two-stage Nerlovian profit inefficiency model. (30th November 2021) - Fukuyama, Hirofumi; Hashimoto, Atsuo; Matousek, Roman; Tzeremes, Nickolaos G.
Highlights: We develop a two-stage network Nerlovian profit inefficiency model. We model human capital on bank's production process. We model in a dynamic framework bank's non-performing loans. We utilize a sample of Japanese local Shinkin banks over the period 2008–2015. We provide evidence of asymmetric effects of human capital on banks' efficiency. Abstract: The paper introduces a two-stage network Nerlovian profit inefficiency estimator, modelling bank' "black box" production processes. The unique features of the model include the modelling of a risk factor measured by period non-performing loans (NPLs). Specifically, NPLs enter in the second stage of banks production processes, alongside a human capital factor. The model is applied to Japanese local Shinkin banks over the period 2008–2015. The findings highlight the importance of incorporating previous period NPLs and human capital factors when modelling bank production processes. Moreover, we provide evidence that previous period NPLs act as an endogenous risk factor having a negative effect on bank profit efficiency levels. The empirical findings suggest that the human capital factor has a positive effect on bank profit efficiency levels. Finally, both the effect of NPLs and human capital factor has an asymmetric effect on bank performance levels.